Sahabat Qur'an (SQ) Parental Control Applications Toward Childrens Worship Through Gadget - Fatahudin, Muhammad; Anas, Ajwar; Ahmadi, Esa (Khalifa Journal of Islamic Education, 2019)
This research aims to design and see the effectiveness of mobile applications Sahabat Qur'an as a means for parents to control their children through gadget. Sahabat Qur'an application is designed using the prototype method through several stages of determining the topic of the problem, designing the application as a solution to the problem, validating the application to experts and end with an application effective test to parents and children as the application user of the Sahabat Qur'an. There are several daily practice features that can be used by parents to control children's worship in the application of Sahabat Qur'an, among others are the reading of Quran, five times praying, recitation of dhikr, prayers and shalawat, and also available Islamic Kazanah articles. The fundamental difference is the one-door communication between parents and children, so that parents can control how the intensity of the child worships through the gadget. Interestingly the app can also detect the position of the child, so parents can control the child's whereabouts wherever they are. After a test of effectiveness and assessment of applications to several users overall stated that the application of Sahabat Qur’an is very useful and also effective as a means for parents to control daily worship of children through the communication of child gadgets. The application design of Sahabat Qur'an is a creative finding in digital technology that has been successfully designed and can even be used, but this application still needs to be developed again to be more effective and innovative.